Triple intervention in congenital wry neck: case report - Munjal, Manish; Munjal, Shubham; Arora, Vineeta; Gill, Karambir; Sharma, Salony; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Loveleen; Sidhu, Kanwarpreet; Pillai, Anjana; Joshi, Tanisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Wry neck or congenital muscular torticollis is consequent to shortened or contracted sternocleidomastoid muscle (SCM). A painless, retracted sternocleidomastoid muscle is the characteristic feature which results in tugging the neck towards affected side, and draws the shoulder upward and forces the chin in the opposite direction. The incidence is between 0.4 to 1.9%. A 17 years old lady with torticollis since childhood is being discussed in detail with the steps of surgical intervention; at three sites to attain a sternocleidomastoid release and resistance free neck and thus a free head movement. This was followed by application of cervical collar, active physiotherapy and postural exercises. The ignorance and improper advice during childhood had led to this marked deformity at adolescence.